2020
DOI: 10.1051/0004-6361/202039434
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic: A chemically anomalous structure in the Galactic halo

Abstract: Detailed elemental-abundance patterns of giant stars in the Galactic halo measured by the Apache Point Observatory Galactic Evolution Experiment (APOGEE-2) have revealed the existence of a unique and significant stellar subpopulation of silicon-enhanced ([Si/Fe] ≳ +0.5) metal-poor stars, spanning a wide range of metallicities (−1.5 ≲ [Fe/H] ≲ −0.8). Stars with over-abundances in [Si/Fe] are of great interest because these have very strong silicon (28Si) spectral features for stars of their metallicity and evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 121 publications
(150 reference statements)
1
23
0
Order By: Relevance
“…3) were then inspected to select the real GCs, by comparison with the CMDs of five known Sgr GCs in the region for which we have similar data (NGC 6715, Arp 2, Pal 12, Ter 7, and Ter 8). NGC 6715 is also the largest of these GCs, with a tidal radius of r t = 10 and a mean metallicity of [Fe/H] = −1.30 ± 0.12 dex (Harris 1996, edition 2010, Baumgardt & Hilker 2018Fernández-Trincado et al 2021). We note that Bellazzini et al (2008) argued that NGC 6715 coincides with the nucleus of Sgr, but it is kinematically distinguished from the nucleus.…”
Section: Resultsmentioning
confidence: 74%
“…3) were then inspected to select the real GCs, by comparison with the CMDs of five known Sgr GCs in the region for which we have similar data (NGC 6715, Arp 2, Pal 12, Ter 7, and Ter 8). NGC 6715 is also the largest of these GCs, with a tidal radius of r t = 10 and a mean metallicity of [Fe/H] = −1.30 ± 0.12 dex (Harris 1996, edition 2010, Baumgardt & Hilker 2018Fernández-Trincado et al 2021). We note that Bellazzini et al (2008) argued that NGC 6715 coincides with the nucleus of Sgr, but it is kinematically distinguished from the nucleus.…”
Section: Resultsmentioning
confidence: 74%
“…Therefore, their Si abundance could be astrophysical rather than artificial. Fernández-Trincado et al (2020) recently suggested that there is a population of stars in the inner halo with enhanced [Si/Fe] ratios and that the population is remnants of globular clusters being disrupted.…”
Section: Abundances: Resultsmentioning
confidence: 99%
“…Regarding the metal-rich ([Fe/H] > -1.0) in situ pop-ulation in the Na-high and Na-extreme subgroups, we note that these may be related to the metal-rich ([Fe/H] > -0.7) population recently discovered from APOGEE data by Fernández-Trincado et al (2021). These authors claimed that this population is likely to be stellar debris from partially or fully disrupted metal-rich GCs.…”
Section: Resultsmentioning
confidence: 61%